Penguatan Literasi Mitigasi Bencana dan Ketahanan Sanitasi melalui Pendekatan Multi-Grade Lintas Generasi di Desa Sekumur, Kecamatan Sekerak, Kabupaten Aceh Tamiang - Mudayat Mudayat; Andayani Andayani; Tepati Hak Kewajiban; Ichwan Ichwan; Izzul Fatawi; Heri Kurniawan; Elang Krisnadi; Eka Wirajuang Daurrohmah; Ikhsan Ikhsan; Muhammad Daud (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Sekumur Village, Sekerak District, Aceh Tamiang Regency is a highly vulnerable area to flash floods and acute environmental sanitation problems. The hydrometeorological disaster at the end of 2025 destroyed almost all residential infrastructure, leaving approximately 300 households in extreme emergency conditions with minimal access to clean water and basic sanitation facilities. This Community Service Program (PkM) aims to strengthen disaster mitigation literacy and community sanitation resilience through an intergenerational multi-grade approach involving children, adolescents, parents, and the elderly. Methods applied include Participatory Rural Appraisal (PRA)-based participatory education, family hygiene kit distribution, psychosocial intervention through trauma-informed pedagogy, and communal asset governance assistance. The program is implemented over ten months (February–November 2026) through four systematic phases. Expected outcomes include enhanced community knowledge on disaster mitigation and healthy sanitation practices, sustainable formation of clean and safe living behaviors, and the establishment of a replicable intergenerational community education model for other disaster-prone areas